2011
DOI: 10.1071/ah09783
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the coding of complications in Queensland and Victorian admitted patient data

Abstract: Our findings demonstrate that the coding of complications is more comprehensive in Victoria than in Queensland. It is known that inconsistencies exist between states in routine hospital data quality. Comparative use of patient safety indicators should be viewed with caution until standards are improved across Australia. More exploration of data quality issues is needed to identify areas for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Also, as described by the CHADx authors, the complications arising from this group of patients are handled differently in the classification system. 12 These important differences affect the exposure of interest (ie, risk of experiencing a hospital-acquired complication) and the main outcome measure (ie, hospital LOS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as described by the CHADx authors, the complications arising from this group of patients are handled differently in the classification system. 12 These important differences affect the exposure of interest (ie, risk of experiencing a hospital-acquired complication) and the main outcome measure (ie, hospital LOS).…”
Section: Methodsmentioning
confidence: 99%
“…24 In addition, classification systems based on coded data are influenced by variations in the accuracy and completeness of clinical documentation and coding between hospitals and jurisdictions. 12 Even with these limitations, we have found that reporting hospital-acquired complications using the CHADx system is valuable in understanding and describing the incidence and effects of such complications in our hospitals. Studying the patterns of these outcomes may help clinicians provide more expert care and help hospital administrators to target resources to areas where care could be improved.…”
mentioning
confidence: 99%
“…Such criticisms are often due to misunderstandings about the strengths and limitations of a standardised and replicable classification system. It has long been argued that variable investment in coding effort across the state-based public hospital systems has led to inconsistencies in data quality in some areas (Michel 2008). Despite this, data audits conducted in Victoria have shown the data to be valid and reliable (Henderson, Shepheard & Sundararajan 2006), and Western Australia and Queensland have taken steps based on auditors' comments to improve the quality (Stevens et al 1998;Logan et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The study illustrated the fact that for any research conducted, careful interpretation of the data is required due to the periodic update of the classification and coding standards. In addition, the coding rules often differ between states and this must be considered prior to comparing state data (Michel 2008). Interpretation of coded data should be carried out with advice from a trained clinical coder or Health Information Manager to ensure comparability of data over time.…”
Section: Patient Safety and Qualitymentioning
confidence: 99%
“…Certainly, the length and depth of coder training varies by state and by region (Michel, Cheng & Jackson 2011), but most Australian hospitals employ tertiary-qualified Health Information Managers (HIMs) as coding supervisors. This role entails ongoing quality assurance within a health information department.…”
mentioning
confidence: 99%